Diagnostic Value of Ascitic Tumor Markers for Gastric Cancer-associated Malignant Ascites - Yaewon Yang; Hong Jun Kim; Se-il Go; Woo Kyun Bae; Eun-Kee Song; Seonggyu Byeon; Hee Kyung Kim; Yusook Jeong; Jihyun Kwon; Ki Hyeong Lee; Hee Bok Chae; Seung-Myoung Son; et al. (Yong Chan Lee, 2022)
Background/Aims Peritoneal carcinomatosis with malignant ascites is common in patients with advanced gastric cancer (GC). The detection of tumor cells is the gold standard for the diagnosis of malignant ascites; however, it often requires complementary tests because of its low sensitivity. Herein, we measured the levels of tumor markers in the malignant ascites of GC patients (GC-ascites) and benign ascites of liver cirrhosis patients (LC-ascites) to elucidate the diagnostic value of tumor markers in GC-ascites. Materials and Methods The levels of CEA, cancer antigen 72-4 (CA 72-4), CA 19-9, and CA 125 were measured in 138 GC-ascites and 64 LC-ascites samples obtained from the National Biobank of Korea. We performed receiver operating characteristic curve analysis to determine the optimal cutoff value for each tumor marker. Results CEA, CA 72-4, and CA 19-9 levels were significantly higher in GC-ascites than in LC-ascites. There was no difference in tumor marker levels between GC-ascites samples irrespective of cytology. CEA, CA 72-4, and CA 19-9 had sensitivities of 85.5%, 79.0%, and 61.6%, respectively, and specificities of 96.8%, 100.0%, and 89.1%, respectively, for distinguishing GC-ascites samples from LC-ascites samples. The diagnostic accuracy was improved by combining two or more tumor markers. The combination of CEA and CA 72-4 showed the highest sensitivity (86.2%) and specificity (100%). Conclusions Measurement of tumor markers, such as CEA, CA 72-4, and CA 19-9, in ascites samples could help diagnose GC-ascites, and combining two or more tumor markers could further increase the diagnostic yield, even in cytology-negative patients.